Evaluation of Lipocalin-2 and Visfatin, and Vitamin (D,C, and E) in Serum of Diabetic Patients with Chronic Periodontitis - Anas Qahtan Hamdi; Entedhar R. Sarhat; Nagham Hasan Ali; Thuraia Rifaat Sarhat (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: The aim of the present study is to verify the hypothesis that salivary and serum lipocalin-2and visfatin, and vitamin (D,C, and E) used as indicators for chronic periodontitis among DMT2 patients.Subjects and methods: We enrolled 41 type 2 diabetic patients with chronic periodontitis -18 males and 23females, aged 60± 14 years and 49 controls- 26 males and 23 females, aged 61.8 ± 12.5 years. Blood sampleswere collected after an overnight fast and routine biochemical parameters such as glucose, lipocalin-2 andvisfatin, and vitamin (D,C, and E)were determined in all samples. Data were considered significant at a levelof p < 0.05.Periodontitis status was established using classic clinical parameters, Plaque index (PI), gingivalindex (GI), probing depth (PD) and clinical attachment level (CAL). Results: 1) The mean serum of bloodglucose, Visfatin, and LCN2 were higher in patients group than in those with normal control group (P<0.001for all comparisons) ; 2) patients with had a lower Vitamin D,C, and E than those with a normal group (P <0.001 for all comparisons).Conclusions: The activity of lipocalin-2 and visfatin in saliva and serum can beuseful in diagnosis, monitorization and treatment of this disease. Further studies are needed to elucidate therole of lipocalin-2 and visfatin in periodontitis and systemic disease interactions.